2014
DOI: 10.1002/adsc.201300801
|View full text |Cite
|
Sign up to set email alerts
|

On the Involvement of a Spiroepoxide Intermediate in N‐Heterocyclic Carbene (NHC)‐Catalyzed Benzoin Condensations – An Approach by Oxygenation of Deoxy‐Breslow Intermediates

Abstract: The involvement of a spiroepoxide, an isomer of the Breslow intermediate, in the catalytic cycle of the N-heterocyclic carbene (NHC)-catalyzed benzoin condensation was suggested by S. Gronert in 2007, based on calculations. To test this hypothesis, enediamines were generated in situ from (in part 13 C-labeled) N-heterocyclic carbenes, benzyl bromide and base, and subsequently treated with various single-oxygen atom oxidants. Clean oxidation occurred with a triazolylidene-derived enediamine and an N-sulfonyloxa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(8 citation statements)
references
References 34 publications
(47 reference statements)
1
7
0
Order By: Relevance
“…4). The calculated high stability of 2c is consistent with the isolation of a ketone structure in benzoin condensation studies by Berkessel and co-workers in 2010 [28,50,53,54].…”
Section: Benzoin Condensation Reaction and Mssupporting
confidence: 88%
See 1 more Smart Citation
“…4). The calculated high stability of 2c is consistent with the isolation of a ketone structure in benzoin condensation studies by Berkessel and co-workers in 2010 [28,50,53,54].…”
Section: Benzoin Condensation Reaction and Mssupporting
confidence: 88%
“…Other possible structures include the ketone 2c and the epoxide 2d (Fig. 2) [28,30,41,[50][51][52][53][54]. MS/MS of m/z 326 yields m/z 311 (loss of CH 3 • ) and m/z 220 (catalyst 1) as the two strongest signals, with the m/z 311 signal being more than twice that of m/z 220.…”
Section: Benzoin Condensation Reaction and Msmentioning
confidence: 97%
“…Gronert performed quantum chemical analysis which indicated that epoxide intermediate is more stable than the zwitterionic species in thiazole containing systems . Berkessel and Elfert tried to identify spiro epoxides from 1,2,4‐triazole‐5‐ylidenes and concluded that there is no trace of epoxide formation . It is possible to identify the epoxide isomers of the BIs on the PE surface of these species, the estimated Δ E E–e (Energy difference between BI and its epoxide isomer) values for BI1 – BI8 are in the range of 9–12 kcal/mol.…”
Section: Resultsmentioning
confidence: 99%
“…As a final note, it should be stressed that NHOs are structurally identical with so-called deoxy-Breslow intermediates, which are frequently encountered in NHC-mediated organo­(polymerization)­catalysis. These intermediates have been identified as crucial for a number of important applications, including polymerization or dimerization of Michael-acceptor systems such as methyl methacrylate and many others. Since the (re)­generation of deoxy-Breslow intermediates/NHOs is a key aspect in these transformations, it can be assumed that the same factors which regulate the PA will also play a role in these cases. Interestingly, Mayr has investigated some NHO structures for their reactivity toward electrophiles and found that the nonsaturated imidazole-derivatives are much more reactive than their saturated counterparts .…”
Section: Comparison With the Pa Of Other Organocatalysts And Correlat...mentioning
confidence: 99%